HIGH INCIDENCE OF OSTEOPOROSIS IN CHRONIC LIVER DISEASE BEFORE LIVER TRANSPLANTATION - CHUGHTAI, T; KHAN, AR; RAZA, A (Biological and Clinical Sciences Research Journal, 2023)
A prospective study was conducted in Nishtar Medical Hospital from January 2022 to January 2023 to assess the incidence of osteoporosis before liver transplant in patients with chronic liver disease. A total of 70 patients were included in the study. A liver biopsy was used to confirm the hepatological diagnosis. Dual-energy X-ray absorptiometry through a densitometer was used for measuring bone mineral density. Results showed that the prevalence of osteoporosis at the femoral neck and lumbar spine was 37%, and in only 14.3% of cases, bone density at these sites was normal. More patients had osteopenia and osteoporosis at the femoral neck (41.7%) compared to the lumbar spine (24.2%) (P=0.009). Osteoporosis was not associated with the severity of the disease; its prevalence was 39%, 32%, and 36% in those with Child-Pugh A, B, and C, respectively (P=0.78). Lower weight (P=0.0007) and increasing age (P=0.038) were independent risk factors for osteoporosis during chronic liver disease. Results show that osteoporosis is highly prevalent in subjects with chronic liver disease before a liver transplant score.